Case Report: Gene Heterogeneity in the Recurrent and Metastatic Lesions of a Myxoid Chondrosarcoma Patient With Aggressive Transformation - He, Xuanhong; Wang, Yitian; Zou, Chang; Zheng, Chuanxi; Luo, Yi; Zhou, Yong; Tu, Chongqi (Frontiers in Genetics, 2022)
Extraskeletal myxoid chondrosarcoma (EMC) is a rare soft tissue sarcoma. In view of the indolent course throughout the prolonged natural history of EMC, it was considered as a low-grade soft-tissue sarcoma. However, recent studies have revealed a high recurrence and metastatic potential in EMC, and the invasiveness of EMC may progress during the protracted clinical course. The mechanism for this aggressive transformation remains unknown. Here, we present a rare case of EMC with aggressive behavior. This case was confirmed via pathology and NR4A3 fluorescent in situ hybridization. To verify the genetic characteristics of this rare case, a total gene sequencing analyses was performed in the recurrent and metastatic lesions. Intriguingly, different gene mutations were determined in the recurrent and metastatic lesions, which implied the genetic heterogeneity among the different lesions might be related to the aggressiveness of EMC. Furthermore, we discuss a few potential agents against the mutated genes in this case, which may provide novel insights regarding the targeted therapy of EMC.